Obesity, family units and social marketing intervention: evidence from Nigeria - Nwoba, Arinze Christian; Mogaji, Emmanuel; Zahoor, Nadia; Donbesuur, Francis; Alam, Gazi Mahabubul (Emerald Publishing, 2022)
Purpose: Building on the social marketing theory, this study aims to examine the relationship between family units and obesity in Nigeria; and the social marketing interventions used to reduce and prevent obesity in the Nigerian society. Design/methodology/approach: This study adopted a semi-structured interview research design with 42 obese individuals in Nigeria. Findings: The study findings show that the family unit an individual grows up in influences their consumption behaviour, which drives their obesity. The findings reveal that obese Nigerian citizens are willing to live a healthier lifestyle due to the direct and indirect medical costs associated with obesity. Furthermore, the findings disclose the social marketing interventions – local celebrity endorsements, healthy lifestyle promotions, reduced gym membership and affordable access to healthy foods and services – used to prevent and reduce the rising obesity rates in the Nigerian society. Research limitations/implications: The findings have important theoretical implication given the focus on consumption behaviour and obesity. Practical implications: The study findings provide an avenue to guide government officials, policymakers and social marketers in shaping their public policy and social marketing interventions to encourage healthier consumption and lifestyle behaviours among families and individuals in the Nigerian society. Originality/value: To the best of the authors’ knowledge, this is the first research study to investigate how family units in the emerging market of sub-Saharan Africa drive obesity and the social marketing interventions used to reduce and prevent obesity. Theoretical and practical implications are discussed.